Knowledge and Awareness about Medical Ethics among Medical Practitioners in a Teaching Medical College and Hospital, Chennai (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: The purpose of this study is to assess the knowledge and awareness towards medical ethics among medical practitioners. The results of this study may be used to guide the tutors of medical students, curricula designers and to bring change in attitude among the doctors towards the patient. Methods: This descriptive, cross-sectional analytic study was conducted to assess the knowledge and awareness towards medical ethics among medical practitioners. A pretested semi-structured questionnaire was given and collected from the participants. After obtaining the data, it was entered in excel spreadsheet and was analysed using SPSS software and frequencies and percentages were obtained. Results: Most of the participants have gained their knowledge on medical ethics from seminar and workshops (40%) and clinical training (36%) followed by other sources such as journal, lectures, ethical books etc., 71% of the participated medical practitioners agreed that “During treatment , the patient’s wishes must always be adhered to”. 66% of the participants disagreed that “Privacy of one patient may be ignored for the benefit of the larger group”. Conclusion: This study highlights the lack of improvement in ethics awareness corresponding to increasing exposure to medical education in the last few years. Thus, with the help of the results obtained from this study, it can be used to devise means to sensitize them to these issues and appropriately training them.